PENGEMBANGAN PENDIDIK DAN TENAGA KEPENDIDIKAN GUNA PENINGKATAN KINERJA DI KAMPUS SWASTA BALANGAN - Erlina, Faridawati (JURNAL KINDAI, 2025)
This study aims to analyze the role of educator and educational staff development in improving learning quality at Sapta Mandiri University, Balangan. The research employed a qualitative method with a case study approach. Data were collected through in-depth interviews with lecturers from various career levels and participatory observation of students. The findings indicate that the university strategically positions educator and staff development as a key instrument for enhancing learning quality, integrated within the implementation of the Tri Dharma of Higher Education. This development includes strengthening pedagogical and professional competencies through innovative teaching methodology training, academic seminars, and Student-Centered Learning (SCL) workshops; improving research capacity through grant proposal writing and journal publication training; and reinforcing community service activities focused on solving local community problems in alignment with Balangan local government programs. Keywords: : educator development, educational staff, learning quality